A critical note on Mcbrearty and Brooks (2000) “The revolution that wasn’t” - Víctor Manuel LONGA MARTÍNEZ (Zephyrus, 2010)
McBrearty and Brooks (2000) provide us with a very important review of the African archaeological evidence. Two core claims are offered from that review: (1) modern behavior emerges gradually, not abruptly; and (2) it emerges in Africa, not in Europe. According to both claims, McBrearty and Brooks criticize the “human revolution” model. My paper aims at showing that the second claim is not denied by any of the proponents of such a model. In fact, all of them consider modern behaviour to have emerged in Africa, not in Europe.